2005
DOI: 10.2174/1568026053828376
|View full text |Cite
|
Sign up to set email alerts
|

Key Aspects of the Novartis Compound Collection Enhancement Project for the Compilation of a Comprehensive Chemogenomics Drug Discovery Screening Collection

Abstract: The NIBR (Novartis Institutes for BioMedical Research) compound collection enrichment and enhancement project integrates corporate internal combinatorial compound synthesis and external compound acquisition activities in order to build up a comprehensive screening collection for a modern drug discovery organization. The main purpose of the screening collection is to supply the Novartis drug discovery pipeline with hit-to-lead compounds for today's and the future's portfolio of drug discovery programs, and to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 108 publications
(141 reference statements)
0
38
0
Order By: Relevance
“…As the profiling panel contains a large number of GPCR targets, previously published work suggested to find such privileged substructures in promiscuous compounds. [22][23][24] Other substructures were checked, but were not significantly prominent in one group or the other. Carboxylic acids show a high selectivity that is probably due to the possible negative charge of the carboxylate group which can lead to unfavorable interactions with most targets of the current in vitro safety panel.…”
Section: Discussionmentioning
confidence: 99%
“…As the profiling panel contains a large number of GPCR targets, previously published work suggested to find such privileged substructures in promiscuous compounds. [22][23][24] Other substructures were checked, but were not significantly prominent in one group or the other. Carboxylic acids show a high selectivity that is probably due to the possible negative charge of the carboxylate group which can lead to unfavorable interactions with most targets of the current in vitro safety panel.…”
Section: Discussionmentioning
confidence: 99%
“…In all virtual screening studies, test sets that consist of compounds selected from databanks are enriched, by using a cluster of compounds that have previously been experimentally proven to be active on the related target. When the ratio of active compounds in the test set is known and when the correct pose is determined, it is possible to measure statistically and numerically the quality of a hypothesis that is screening based by using methods such as receiver operating characteristic (ROC) curves [15][16][17][18] .…”
Section: Figure 2: the Active Site-ligand Interactions In E Colimentioning
confidence: 99%
“…Jacoby and coworkers published a detailed analysis of their experience at Novartis [12]. They found that the validated hit rate of the combinatorial collection was 0.02 percent.…”
Section: Screening Librariesmentioning
confidence: 99%